Pelo espaço concebido: as repercussões dos modelos do urbanismo moderno na (re)produção do espaço urbano de Belo Horizonte - Reginaldo Magalh?es de Almeida (2014)
Knowledge of Urban Science, termed as "models of modern urbanism" were disseminated in Brazil, in the twentieth century, and had a significant influence on the production of space in Brazilian cities. The main issue of this thesis is to reflect on the influence of models of modern urbanism in certain conceptions of urban expansion in the form of linked installment, which contribute to the (re) production of the belo-horizontino abstract space. This space constructed according to capitalist referred to as abstract logic. Thus, develops a critical analysis of the (re) production of capitalist urban space, based on Henri Lefébvre, and the theoretical categories of the models of modern urbanism, revealed by Françoise Choay. Subsequently, there will be a critical study on urban expansions Belo Horizonte, since the genesis of the city until the first decade of the XXI century, in order to establish a dialogue between the strands of modern urbanism and lefebvrianas assumptions about the (re) production of urban space. It was used for the analysis, among others, the Cadastral Plans and Administrative Procedures contained in the Prefecture of Belo Horizonte. The study converges to three recent methods of land division of Belo Horizonte, in the implementation process: a scientific and economic, Parque Tecnológico de Belo Horizonte; other, mainly economic, Granja Werneck, and a housing of the Minha Casa Minha Vida program called Victory II Subdivision. The analysis of these three expansions contributed to ascertain that the science of modern urbanism, especially certain key ideas of the progressives, naturalist and culturalist models are still present, contributing to the fragmentation, homogenization and hierarchy of urban space in Belo Horizonte, increasingly rarer.